2022
DOI: 10.3390/ijms232315250
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Hormones in Hidradenitis Suppurativa: A Systematic Review

Abstract: Hidradenitis suppurativa (HS) is a chronic inflammatory disease manifesting in inverse body regions. In a systematic review, the role of hormones in HS will be presented to better understand the pathomechanisms of HS. The review is based on the PRISMA criteria. Systematic research was carried out using keywords. Subsequently, the data were analyzed based on the clinical response and other relevant information. The main focus of our systematic review was on HS manifestation, exacerbation, sex hormones, antiandr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
28
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(29 citation statements)
references
References 85 publications
1
28
0
Order By: Relevance
“…Thus, on the one hand, further prospective studies are needed to determine whether anti-inflammatory therapy in HS patients influences insulin sensitivity and disease severity. On the other hand, many case series and reports show improvement in HS disease severity in patients on antidiabetic medication [ 5 , 10 ]. This further suggests that the disease severity of DM and HS may be, at least partially, linked through common mechanisms and negatively impact each other, presumably by promoting chronic inflammation in a vicious, proinflammatory circle.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, on the one hand, further prospective studies are needed to determine whether anti-inflammatory therapy in HS patients influences insulin sensitivity and disease severity. On the other hand, many case series and reports show improvement in HS disease severity in patients on antidiabetic medication [ 5 , 10 ]. This further suggests that the disease severity of DM and HS may be, at least partially, linked through common mechanisms and negatively impact each other, presumably by promoting chronic inflammation in a vicious, proinflammatory circle.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, our results highlight the importance of adipose tissue as an endocrine organ in the evolution of HS. Some studies in HS showed a disbalance of adipokines compared to the control subjects, independently of BMI [ 5 ]. We propose that adipose tissue in HS should be further investigated regarding its function and structure.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The most common comorbidities in our HS collective were obesity (59.5%), hypertension (29.8%) and diabetes mellitus (19.8%). Indeed, it is well‐established that a disproportionately high number of HS patients suffer from obesity, metabolic syndrome, and insulin resistance 2,3,24 . Future studies into Hp‐phenotyping might provide a mechanistic link between the prevalence of these metabolic alterations and HS pathogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…Aggravating, burdensome pain and itching as well as a malodourous discharge are the leading symptoms among patients with HS [3][4][5]. Up until now, the topic of the etiopathogenesis of this disease is being studied, although research on the main origin leans towards an autoinflammatory and genetic as well as a suspected hormonal background [6][7][8]. Additionally, HS patients usually present with other comorbidities such as, obesity and metabolic syndrome [9,10].…”
Section: Introductionmentioning
confidence: 99%